Correction: Promotional mechanism of enhanced denitration activity with Cu modification in a Ce/TiO2–ZrO2 catalyst for a low temperature NH3-SCR system. Issue 3 (10th January 2022) - Zhang, Wei; Tang, Yunhao; Xiao, Wei; Ruan, Min; Yin, Yanshan; Song, Quanbin; Xie, Kang; Qin, Chuan; Dong, Mengyao; Zhou, Yunhe; Li, Jie
Abstract : Correction for 'Promotional mechanism of enhanced denitration activity with Cu modification in a Ce/TiO2 –ZrO2 catalyst for a low temperature NH3 -SCR system' by Wei Zhang et al., RSC Adv., 2022, 12, 378–388, DOI: ; 10.1039/d1ra06325a